2016
DOI: 10.1073/pnas.1607795113
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human Niemann–Pick C1 protein

Abstract: Niemann-Pick C1 protein (NPC1) is a late-endosomal membrane protein involved in trafficking of LDL-derived cholesterol, Niemann-Pick disease type C, and Ebola virus infection. NPC1 contains 13 transmembrane segments (TMs), five of which are thought to represent a "sterol-sensing domain" (SSD). Although present also in other key regulatory proteins of cholesterol biosynthesis, uptake, and signaling, the structure and mechanism of action of the SSD are unknown. Here we report a crystal structure of a large fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
153
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 51 publications
3
153
1
Order By: Relevance
“…Structural insights into NPC1 function have been reported by several groups since 2009: (i) An isolated N-terminal fragment of NPC1 presenting the NTD harbors a cholesterol molecule consistent with previous biochemical observations (19); (ii) a complex of the MLD and Ebola glycoprotein defines the site of Ebola virus attachment (20); (iii) a near-atomic X-ray structure of NPC1 (residues 314-1,278, termed NPC1*) shows that the SSD may indeed accommodate a cholesterol molecule (21); (iv) a cryo-EM…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Structural insights into NPC1 function have been reported by several groups since 2009: (i) An isolated N-terminal fragment of NPC1 presenting the NTD harbors a cholesterol molecule consistent with previous biochemical observations (19); (ii) a complex of the MLD and Ebola glycoprotein defines the site of Ebola virus attachment (20); (iii) a near-atomic X-ray structure of NPC1 (residues 314-1,278, termed NPC1*) shows that the SSD may indeed accommodate a cholesterol molecule (21); (iv) a cryo-EM…”
supporting
confidence: 78%
“…We expressed and purified the NPC1* (residues 314-1,278) as previously published (21). A previous photo-crosslinking study showed itraconazole binds to NPC1 in vitro (15).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, both the N-terminal domain and lumenal domain 2 are likely to interface with NPC2 as part of the cholesterol transfer process (12,13,20). Both the cryo-EM and crystal structures highlight the unusual height of the protein in relation to the lysosome's internal limiting membrane (5,20). This height may serve to provide a cholesterol transfer mechanism that can enable cholesterol to be passed through the glycocalyx that lines the limiting membrane.…”
mentioning
confidence: 99%
“…In addition to its important role in cholesterol transport, NPC1 has also been identified as a key component required for the entry of Ebola virus into the cytoplasm (3,4). In PNAS Li et al (5) present a 3D structural model of NPC1, which provides important new clues to the mechanisms by which cholesterol is exported from lysosomes and the mechanism by which Ebola virus docks on the internal surface of the lysosome-limiting membrane as part of the infection process.…”
mentioning
confidence: 99%
See 1 more Smart Citation